Curcumventing the Menthol Ban: Internet sales of menthol balls - AY, NADİYE PINAR (My University, 2022)
Aim: Menthol makes smokers inhale more deeply and increase exposure time with its cooling effect on the airways. Use of menthol in tobacco products was banned in Turkey since 5th January 2022. This study aims to investigate the internet sales of a new product called "menthol ball" which is made to inject menthol into regular cigarettes. Method: “Menthol Ball" key word was Google searched. Out of 45,500 data retrieved 1696 relevant ones were further investigated. Web sites of the products, e-commerce websites,social media accounts were detected. Their promotional activities, methods of trading were noted. Results: 37 brands of menthol balls were detected. All brands promote their products through videos describing the injection of the tiny menthol balls into the classical cigarettes. Only 12 have their individual website, the other 25 use main e-commerce outlets to reach to the customers. Two menthol ball brands market their products in one-kilogram bags at e-commerce sites. One brand market a "menthol ball liquid" for roll-your-own tobacco. Three major e-commerce sites sell 1485 different flavored menthol balls under the category of air refresher. One other e-commerce site sold 88 various menthol balls under the category of tobacco bags. Conclusion: Banning menthol in tobacco products help prevent youth starting to smoke or lower smoking rates among vulnerable communities . However freely sold menthol that can be injected into the cigarettes may reincarnate menthol cigarettes. Any product that will circumvent menthol ban must be restricted.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Health Sciences; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine